Investigation on the shear cutting of functional components manufactured in an orbital forming process - Hetzel, Andreas; Lechner, Michael; Merklein, Marion (Materials Research Proceedings, 2023)
Applying forming operations for the manufacturing of complex functional components instead of conventional shearing or milling is an effective way to increase the material efficiency of the process as well as the mechanical properties of the part. Nevertheless, in many cases subsequent cutting operations are mandatory to reach the final geometry or to add functional surfaces for the later assembly. During forming, hardening effects or different strain states can cause difficulties for the subsequent cutting operation. These characteristics are commonly determined for sheet metal forming processes like deep drawing or bending. However, the complex stress and strain states during sheet-bulk metal forming operations and their influence on the cutting parameters or the part properties have not been investigated comprehensively so far. Furthermore, different assigned processes, like for example orbital forming, allow a local material distribution, realizing a gradient in sheet thickness. Therefore, this contribution focuses on the establishment of a fundamental process understanding on the influence of a sheet-bulk metal forming process on the cutting parameters and the resulting part properties. Functional components are manufactured from C10 sheet metal by orbital forming and subsequently shear cut to generate the final contour. During cutting, specific force-stroke diagrams are evaluated, in order to analyze the influence on the process parameters. The resulting properties of the parts are investigated regarding the quality of the cutting surface and a potential geometrical distortion in consequence of elastic spring back. The influence of the forming process is outlined by a direct comparison with conventionally cut components.<br
Keywords: Metal forming; Cutting; Orbital forming